'Wacky' patents meet economic indicators - Dirk Czarnitzki; Katrin Hussinger; Cédric Schneider (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
This study investigates whether standard patent measures for the importance and basicness of patents are able to distinguish between 'wacky' patents and a control group of randomly drawn patents. Our findings show that forward citations are good predictors of importance. However, the 'wacky' patents have higher originality, generality and average citation lags than the controls, which suggests that these indicators should be interpreted carefully.
urn:nbn:de:bsz:180-madoc-31980
Keywords: O34; 330; patents; patent indicators; quality measurement